Pengelolaan Wakaf Produktif dalam Membentuk Mutu Pendidikan Madrasah Diniyah : Productive Waqf Management in Forming the Quality of Madrasah Diniyah Education - Mas'ud, Ali; Hamidah, Tutik; Sudirman, Sudirman (STAI Publisistik Thawalib Jakarta, 2024)
This study discusses the implementation of productive waqf in an effort to improve the efficiency and effectiveness of the education system in Madrasah Diniyah. The purpose of the study is to identify and evaluate the implementation of productive waqf in supporting the improvement of education in madrasahs. This research approach implements qualitative with a case study design. Data were obtained through in-depth interviews, observations, and document analysis. The results of the study indicate that productive waqf plays an important role in improving the financial independence of madrasahs, thus contributing to a more optimal allocation of resources for operations, teacher welfare, and improving educational facilities. In addition, the strategic use of waqf funds for technology development and infrastructure improvements has been shown to have a positive impact on improving student academic achievement and increasing teacher professional capacity. This evaluation highlights the importance of efficient resource management and the integration of modern educational technology in improving the overall quality of the education system.